Fundamentals of multimedia - Zeki, Akram M.; Badi, Maimona J.; Abubakar, Adamu (IIUM Press, 2015)
The term Multimedia is a combination of two words "Multi" and "Media". Multi is a short form for multiple, which stands for many or several countable things. Media stands for different digital information formats that can be presented to the users electronically. Therefore, we can simply say that, a combination of two or more media is a multimedia. It is defined as a collection of texts, sounds, images, animations and video delivered to the users electronically in a digital format. Overall, multimedia includes everything we see, hear, read or touch, mostly in the form of image/picture, sound, audio, video, records, films, animations or more.